What Does Dynamics of Tourism Marketing Show in 12 Developing Countries? - Vanegas, Manuel A (Journal of Developing Economies, 2021)
This study is motivated by the idea to what extent tourism marketing investment contributes to tourism demand expansion. It searches for better estimation methods that can deal with the inter-temporal and cross-section correlation of the disturbances. The effect of omitting the tourism marketing variable, as evidenced by the drastic change in long and short-run elasticity values for all tourism demand models, has emerged clearly. There is a need for the national tourism institutions to have a clear, consistent, and sustained investment policy in tourism marketing activities with respect to enhanced effectiveness in allocating financial resources.Keywords: Tourism Marketing, 12 Developing Countries, Dynamic Panel, Elasticity Values, Omission of Tourism Marketing Variable.JEL: Z33, C23,O50